A computational tool suite to facilitate single-cell lineage tracing analyses - Waterfall, Joshua J.; Midoun, Adil; Perié, Leïla (Cell reports methods, 2024)
Tracking the lineage relationships of cell populations is of increasing interest in diverse biological contexts. In this issue of Cell Reports Methods, Holze et al. present a suite of computational tools to facilitate such analyses and encourage their broader application. Tracking the lineage relationships of cell populations is of increasing interest in diverse biological contexts. In this issue of Cell Reports Methods, Holze et al. present a suite of computational tools to facilitate such analyses and encourage their broader application.